2006
DOI: 10.1002/etep.105
|View full text |Cite
|
Sign up to set email alerts
|

Feedforward neural network-based transient stability analysis of electric power systems

Abstract: SUMMARYThis paper presents a neural approach for the transient stability analysis of electric power systems (EPS). The transient stability of an EPS expresses the ability of the system to preserve synchronism after sudden severe disturbances. Its analysis needs the computation of the critical clearing time (CCT), which determines the security degree of the system. The classical methods for the determination of the CCT are computation time consuming and may be not treatable in real time. A feedforward neural ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…Previous studies [19] have shown that the CCT can be approximated with high accuracy, based on the load flow data, using a polynomial function. For the purpose of CCT approximation, feed-forward ANNs have been used in many studies [20][21][22][23]. The structure of a feedforward neural network has been thoroughly described in the literature, and is not shown here for brevity.…”
Section: Using the Ann To Approximate The Stability Boundarymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies [19] have shown that the CCT can be approximated with high accuracy, based on the load flow data, using a polynomial function. For the purpose of CCT approximation, feed-forward ANNs have been used in many studies [20][21][22][23]. The structure of a feedforward neural network has been thoroughly described in the literature, and is not shown here for brevity.…”
Section: Using the Ann To Approximate The Stability Boundarymentioning
confidence: 99%
“…This paper proposes an alternative approach to solve the TSC-OPF problem, where the transient stability constraints are approximated using artificial neural networks (ANNs). The study is motivated by previous research, which showed that the CCT can be approximated with very high accuracy from prefault load flow data using various artificial intelligence networks [19][20][21][22]. Hence, the ANNs can provide analytical expressions of the stability boundaries and their sensitivity with respect to optimization variables.…”
Section: Introductionmentioning
confidence: 99%
“…Destaca-se que as RNA são aceitas cientificamente na área de Sistemas Elétricos de Potência para diversas aplicações: estimação da velocidade de máquinas elétricas (Goedtel et al, 2013), estabilidade transitória (Abdallah et al, 2006) e classificação de cargas não lineares (Saraiva et al, 2015).…”
Section: Introductionunclassified
“…Many researchers have suggested the application of machine learning methods for on-line predication of CCT and therefore, transient stability status. The ANNs are the most popular method among machine learning methods and have been proposed for the transient stability assessment [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The transient stability can be assessed by different techniques such as time domain integration [1][2][3], direct methods based on energy function and extended equal area criterion [4][5][6], pattern recognition [7,8], decision trees (DTs) [9,10], and artificial neural networks (ANNs) [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%